INNOVATIVE ACTIVITY OF HUMAN CAPITAL - Myltykbayeva L.A.,; Doskaliyeva B.B., (Academic Journal of Physical and Chemical Sciences, 2020)
The article discusses the transformation of the role of the human factor in the processes of reproduction in an innovative and knowledge-based economy. An analytical comparison of the categories of human capital and human potential was conducted. A new look at the social sphere is indicated, the importance of which in the modern economy has grown and acquired new content as a conductor of investment flows that the government directs to the development of human potential. The level of the national economy receives a macroeffect from investments in human capital, despite the fact that economists tend to ignore the instrumental value of such investments, because the effect obtained by improving the quality of the population is too dispersed, manifested itself after a long time and is difficult to measure. The production potential of new technologies depends on the quality of training systems at the level of qualification that they provide. Growth dynamics of modern innovation and information economy, both global and local, is not determined by a simple increase in production in all sectors, and that part which is generated by a variety of innovative and qualitative changes in the production process of goods and services. Further intensification of the innovative process in recent decades due to the formation of a new type of economic development based on the continuous change of the production base, and the nature of the products with the continuous creation of fundamentally new technologies as well as new types of goods and services. In fact, mastering high-quality skills and experience and improving them creatively becomes a necessary response to changes in production technology and rapidly changing requirements for quality and productivity. Education, health care, vocational training, the search for economically significant information, labor mobility, education and childcare are the main areas of “investment in human capital”. The core of the development of modern competitive countries is the availability of innovative systems and human potential that can support and develop these systems. Despite the conceptual incompleteness of the theory of human capital, a causal relationship between the level of education, healthcare and mobility of human resources and the level of competitiveness of the national economy is scientifically substantiated and recognized by the international community. Accordingly, it remains an indisputable fact that the improvement of the country's human potential occurs in the social sphere, for the activity of which the state bears full responsibility.